Feedback regulation of TGF-β signaling. (8th December 2017) - Yan, Xiaohua; Xiong, Xiangyang; Chen, Ye-Guang
Abstract: Transforming growth factor beta (TGF-β) is a multi-functional polypeptide that plays a critical role in regulating a broad range of cellular functions and physiological processes. Signaling is initiated when TGF-β ligands bind to two types of cell membrane receptors with intrinsic Ser/Thr kinase activity and transmitted by the intracellular Smad proteins, which act as transcription factors to regulate gene expression in the nucleus. Although it is relatively simple and straight-forward, this TGF-β/Smad pathway is regulated by various feedback loops at different levels, including the ligand, the receptor, Smads and transcription, and is thus fine-tuned in terms of signaling robustness, duration, specificity, and plasticity. The precise control gives rise to versatile and context-dependent pathophysiological functions. In this review, we firstly give an overview of TGF-β signaling, and then discuss how each step of TGF-β signaling is finely controlled by distinct modes of feedback mechanisms, involving both protein regulators and miRNAs.